Assessing prosthodontic dental treatment needs in older adults in Thailand: normative vs. sociodental approaches - Srisilapanan P. (2014)
The authors compared the estimated prosthodontic treatment needs of edentulous older adults when using normative and sociodental approaches. This cross-sectional study involved a non-random sample of 158 edentulous adults, aged 60 to 74 years, who were living independently in metropolitan Chiang Mai, Thailand. Each subject was given an oral examination and was interviewed. The dental questionnaire and the clinical criteria were adapted from the National Diet and Nutritional Survey for People Aged 65 and Older and included the Oral Impacts on Daily Performances sociodental indicator. Of the 158 subjects, we found using a normative assessment that 79.7% had a treatment need for complete dentures; 60.5% of those adults had impact-related treatment needs. Estimated treatment need dropped by about 40% when subjects were assessed using the sociodental approach. We concluded that large reductions in normative need estimates for complete dentures were apparent using a sociodental approach to assess prosthodontic dental treatment needs of older people.